2018
DOI: 10.1021/acsomega.8b01215
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Interpenetrating Network-Type Cross-Linked Amphoteric Ion-Exchange Membrane Based on Styrene Sulfonate and Vinyl Benzyl Chloride for Vanadium Redox Flow Battery

Abstract: Clean energy is the main requirement for human life. Redox flow battery may be an alternative to fossil fuels. An ion-exchange membrane is the heart of the redox flow battery. In the present study, we synthesize semi-interpenetrating cross-linked copolymer amphoteric ion-exchange membranes (AIEMs) with a partially rigid backbone. The styrene sulfonate and vinyl benzyl chloride monomers are used as the cationic and anionic moieties into the AIEMs. Three different types of quaternizing agents are used to convert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…The redox couples are VO 2 + /VO 2+ and V 3+ /V 2+ in the anolyte and catholyte compartment, respectively. 17 The IEMs required for VRFB should possess good mechanical and chemical stability, together with good proton conductivity and low crossover of vanadium ions. 18,19 Nafion is the state-of-the-art membrane used for redox flow batteries possessing good proton conductivity and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…The redox couples are VO 2 + /VO 2+ and V 3+ /V 2+ in the anolyte and catholyte compartment, respectively. 17 The IEMs required for VRFB should possess good mechanical and chemical stability, together with good proton conductivity and low crossover of vanadium ions. 18,19 Nafion is the state-of-the-art membrane used for redox flow batteries possessing good proton conductivity and mechanical stability.…”
Section: Introductionmentioning
confidence: 99%
“…In an amphiphilic membrane, the penetration of vanadium ions can be effectively resisted by the cationic groups due to their Donnan exclusion effect, while the anionic groups (sulfonate groups) ensure the high conductivity of membranes. The results reported in the previous papers showed that the amphoteric membranes are good prospects for VRFB applications …”
Section: Introductionmentioning
confidence: 99%
“…Other types of CEMs containing sulfonic acid groups were developed due to their excellent proton conductivity and their mechanical and chemical stabilities. However, a high degree of sulfonation is required to obtain high conductivity, which often leads to high swelling ratio and reduced mechanical stability [123].…”
Section: Energy Storage Devicesmentioning
confidence: 99%
“…Other types of CEMs containing sulfonic acid groups were developed due to their excellent proton conductivity and their mechanical and chemical stabilities. However, a high degree of sulfonation is required to obtain high conductivity, which often leads to high swelling ratio and reduced mechanical stability [123]. This year (2019), Cui, Y. et al prepared a series of amphoteric membranes by preirradiation-induced graft copolymerization of styrene and dimethylaminoethyl methacrylate in an aqueous emulsion media followed by solution casting, sulfonation, and protonation.…”
Section: Energy Storage Devicesmentioning
confidence: 99%